Determinan Nilai Perusahaan Manufaktur di Indonesia - Novita Yana; Khairatun Hisan (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2023)
This study aims to determine the effect of profitability, funding decisions and dividend policies on the value of manufacturing companies listed on the Indonesia Stock Exchange. It is a quantitative study with annual data on profitability, funding decisions and dividend policies on the value of manufacturing companies listed on the Indonesia Stock Exchange. The data analysis method uses panel data linear regression with the E-Views application 9. The results of the partial test with statistical panel data analysis show that the profitability (Return on Assets) has no significant effect on manufacturing company value, the funding decision policy (Debt to Equity Ratio) partially has a positive and significant effect and dividend policy (Dividend Payout Ratio) partially has no significant effect. While simultaneously profitability, funding decisions and dividend policy have a positive and significant effect on firm value.